Labor Reform in Brazil, Politics, and Sindicatos: Notes on the General Strikes of 2017. Issue 2 (August 2019) - Carbonai, Davide
On July 2017, Brazil's Senate approved the country's most extensive labor reform since the emergent 1943's Consolidation of Labor Law (Consolidação das Leis Trabalhistas, CLT). The aforementioned reform provoked heated debates and its approval faced resistance. Unions, for instance, convened two general strikes: the first, on April 2017, garnered a significant amount of participation, while the latter, on June, ended with participation falling significantly below expectations. Despite the widespread rejection of Temer's mandate and the content of the law, on June, unions were surprisingly unable to agree on a common strategy regarding a proposal on labor reform. The present research aims to explore this paradox. A survey-based analysis, along with a series of unstructured interviews with union leaders and protesters, establishes a solid empirical base from which to draw hypotheses about the Brazilian state corporatist union model and its evolution.